2012
DOI: 10.1371/journal.pone.0051076
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Protects against Oxaliplatin-Induced Cell Death via ER Stress and ROS in Caco-2 Cells

Abstract: Oxaliplatin is included in a number of effective combination regimens used as first and subsequent lines of therapy for metastatic colorectal cancer. Accumulating evidence indicates that autophagy plays a significant role in response to cancer therapy. However, the role of autophagy in oxaliplatin-induced cell death remains to be clarified. In this study, we showed that oxaliplatin induced cell death and autophagy in Caco-2 colorectal cancer cells. The suppression of autophagy using either pharmacologic inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 28 publications
3
53
0
Order By: Relevance
“…The findings of the present study are in line with a recent report in which OX was demonstrated to activate autophagy in colon cancer cells via the ER stress and ROS pathways, and inhibition of this autophagy increased cell death upon OX treatment in vitro (13). However, the current study performed an additional step to demonstrate the potential therapeutic efficiency and feasibility in vivo, using a combinational treatment strategy of an autophagy inhibitor and OX in a mouse model.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the present study are in line with a recent report in which OX was demonstrated to activate autophagy in colon cancer cells via the ER stress and ROS pathways, and inhibition of this autophagy increased cell death upon OX treatment in vitro (13). However, the current study performed an additional step to demonstrate the potential therapeutic efficiency and feasibility in vivo, using a combinational treatment strategy of an autophagy inhibitor and OX in a mouse model.…”
Section: Discussionsupporting
confidence: 91%
“…However, autophagy in cancer cells may promote cell survival by sustaining the cellular metabolism necessary for survival under hypoxic conditions and drug treatment, resulting in tumor growth and therapeutic resistance (8)(9)(10). In colon cancer, autophagy appears to favor cancer cell survival by protecting from tumor cell death caused by chemotherapy and radiotherapy (11)(12)(13)(14)(15). For example, it has been demonstrated that autophagy is responsible for the resistance of colon cancer cells to 5-fluorouracil (FU) treatment, as inhibition of autophagy enhances 5-FU-induced tumor cell apoptosis in vitro (11,12,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging role of autophagy has been well demonstrated in colorectal carcinoma in recent times (Yang et al, 2011;Shi et al, 2012;Han et al, 2014). Distinct patterns of expression of autophagy related proteins, viz.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a known hallmark of cancer; vascular insufficiency in tumors may lead to depletion of glucose and/or oxygen and thus contribute to increased reactive oxygen species production, extracellular acidosis in tumor microenvironment eventually resulting in autophagy, thereby implicating glucose depletion and or deprivation (GD) as a crucial trigger for autophagy (Bensaad et al, 2009;Du et al, 2013;Shoji-Kawata et al, 2013). My study hypothesis was that AR inhibition regulated autophagy in colorectal carcinoma.…”
Section: Aldose Reductase Inhibitor Fidarestat As a Promising Drugmentioning
confidence: 98%